Atom probe characterization of precipitation in an aged Cu-Ni-P alloy - Arugan, Y.; Saxey, David; Marquis, E.; Cerezo, A.; Smith, G. (2011)
A temporal evolution of clusters associated with age hardening behavior in a Cu–Ni–P alloy during ageing at 250 °C for up to 100 ks after solution treatment has been carried out. A three-dimensional atom probe (3DAP) analysis has showed that Ni–P clusters are present in the as-quenched condition, and that the cluster density increases as the ageing time increases. The clusters have a wide range of Ni/P ratios when they are relatively small, whereas larger clusters exhibit a narrow distribution of the Ni/P ratio, approaching a ratio of approximately two. These results would indicate that the clusters with various Ni/P ratios form at the early stage of precipitation and the ratio approaches a value identical to that of the equilibrium phase at 250 °C as the clusters enlarge during ageing.